Volatile organic compounds emitted by Burkholderia pyrrocinia CNUC9 trigger induced systemic salt tolerance in Arabidopsis thaliana - Luo, Huan; Riu, Myoungjoo; Ryu, Choong-Min; Yu, Jun Myoung (Frontiers in Microbiology, 2022)
Salinity is among the most significant abiotic stresses that negatively affects plant growth and agricultural productivity worldwide. One ecofriendly tool for broadly improving plant tolerance to salt stress is the use of bio-inoculum with plant growth-promoting rhizobacteria (PGPR). In this study, a bacterium strain CNUC9, which was isolated from maize rhizosphere, showed several plant growth-promoting characteristics including the production of 1-aminocyclopropane-1-carboxylate deaminase, indole acetic acid, siderophore, and phosphate solubilization. Based on 16S rRNA and recA gene sequence analysis, we identified strain CNUC9 as Burkholderia pyrrocinia. Out of bacterial determinants to elicit plant physiological changes, we investigated the effects of volatile organic compounds (VOCs) produced by B. pyrrocinia CNUC9 on growth promotion and salinity tolerance in Arabidopsis thaliana. Higher germination and survival rates were observed after CNUC9 VOCs exposure under 100 mM NaCl stress. CNUC9 VOCs altered the root system architecture and total leaf area of A. thaliana compared to the control. A. thaliana exposed to VOCs induced salt tolerance by increasing its total soluble sugar and chlorophyll content. In addition, lower levels of reactive oxygen species, proline, and malondialdehyde were detected in CNUC9 VOCs-treated A. thaliana seedlings under stress conditions, indicating that VOCs emitted by CNUC9 protected the plant from oxidative damage induced by salt stress. VOC profiles were obtained through solid-phase microextraction and analyzed by gas chromatography coupled with mass spectrometry. Dimethyl disulfide (DMDS), methyl thioacetate, and 2-undecanone were identified as products of CNUC9. Our results indicate that optimal concentrations of DMDS and 2-undecanone promoted growth in A. thaliana seedlings. Our findings provide greater insight into the salt stress alleviation of VOCs produced by B. pyrrocinia CNUC9, as well as potential sustainable agriculture applications.